Bárbara Graziosi, Homer, Oxford University Press, Oxford, 2016, 154 pp. - Zamperetti Martín, Deidamia Sofía (2017)
Fil: Zamperetti Martín, Deidamia Sofía. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.